Особливості концентрації агропромислового виробництва України - Басюркіна, Н.Й. (Економічні інновації, 2013)
У статті на основі аналізу процесів концентрації агропромислового виробництва в Україні виявлено їх причини, тенденції, чинники впливу і ефекти. Показано зв'язок концентрації агропромислового виробництва з його ефективністю. Запропоновано розподіл регіонів за рівнем концентрації. Доведено, що масштабна економічна концентрація супроводжується монополізацією агропродовольчого ринку країни, в зв’язку з чим є необхідним державне регулювання цих процесів на всіх рівнях. In the article of processes reasons, tendencies, factors of influence and effects of concentration of agroindustrial production, are educed in Ukraine on the basis of their analysis. Connection of concentration of agroindustrial production is shown with his efficiency. Distribution of regions is offered after the level of concentration. It is well-proven that a scale economic concentration is accompanied by monopolization of agrarian-food market of country. In this connection government control is a necessity on all levels of processes of concentration of agroindustrial production.